Impaired Cardiac Reserve and Abnormal Vascular Load Limit Exercise Capacity in Chronic Thromboembolic Disease - Claeys, Mathias; Claessen, Guido; La Gerche, Andre; Petit, Thibault; Belge, Catharina; Meyns, Bart; Bogaert, Jan; Willems, Rik; Claus, Piet; Delcroix, Marion (JACC. Cardiovascular imaging, 2019)
This study was a comprehensive evaluation of cardiopulmonary function in patients with chronic thromboembolic (pulmonary vascular) disease (CTED) during exercise. Exertional dyspnea is frequent following pulmonary embolism, but only a minority of patients eventually develops chronic thromboembolic pulmonary hypertension (CTEPH). Better understanding of the factors that limit exercise capacity in patients with persistent pulmonary artery obstruction could help to further define the entity of CTED. Fifty-two subjects (13 healthy control subjects, 14 CTED patients, and 25 CTEPH patients) underwent cardiopulmonary exercise testing and exercise cardiac magnetic resonance with simultaneous invasive pressure registration. Pulmonary vascular function and right ventricular contractile reserve were assessed through combined invasive pressure measurements and magnetic resonance imaging volume measures. Exercise capacity was reduced by 29% and 57% in patients with CTED and CTEPH respectively, compared with control subjects. Both CTED (3.48 [interquartile range: 2.24 to 4.36] mm Hg × l−1 × min−1) and CTEPH patients (8.85 [interquartile range: 7.18 to 10.4] mm Hg × l−1 × min−1) had abnormal total pulmonary vascular resistance. Right ventricular contractile reserve was reduced in CTED patients compared with control subjects (2.23 ± 0.55 vs. 3.72 ± 0.94), but was still higher than that in CTEPH patients (1.34 ± 0.24; p < 0.001). As opposed to patients with CTEPH in whom right ventricular ejection fraction declined with exercise, right ventricular ejection fraction still increased in patients with CTED, albeit to a lesser extent than in healthy control subjects (interaction p < 0.001), which illustrated the distinct patterns of ventricular−arterial coupling. CTED represents an intermediate clinical phenotype. Exercise imaging unmasks cardiovascular dysfunction not evident at rest and identifies hemodynamically significant disease that results from reduced contractile reserve or increased vascular load. [Display omitted]